Drosophila melanogaster larvae control amylase secretion according to the hardness of food - Sakaguchi, Honami; Suzuki, Masataka G. (Frontiers in Physiology, 2013)
Drosophila melanogaster larvae excrete amylase and perform external digestion of their food. In this study, to investigate whether their external digestion ability varies in response to changes in the external environment, we measured the relative amount of amylase excreted by larvae using a new method: the iodine starch agar method (ISAM). Analysis using this method revealed that the amount of amylase excreted by larvae increased in accordance with the increase in the agar concentration. In addition, we investigated the effect on the larval growth rate of adding amylase to the diet. Pupation occurred 24 h later in food containing 1% amylase than in food containing no amylase. These results suggest that the larvae adjust their amylase excretion in response to changes in the external environment, and that its level has a marked influence on the larval growth rate.